The effect of benralizumab on inflammation in severe asthma: a real-life analysis - Visca, Dina; Ardesi, Francesco; Zappa, Martina; Grossi, Sarah; Pignatti, Patrizia; Vanetti, Marco; Pini, Laura; Sotgiu, Giovanni; Centis, Rosella; Migliori, Giovanni Battista; Spanevello, Antonio (Therapeutic advances in respiratory disease, 2024)
Background: Benralizumab is a monoclonal antibody treatment for severe eosinophilic asthma (SEA). Few studies investigated its role in airway inflammation and its correlation with lung function. Objectives: The aim of the present study is to assess its effect after 1 year of treatment, focusing on airway inflammation. Design: This is a retrospective observational study, in an Italian tertiary reference centre specialised in diagnosis and management of severe asthma patients. Methods: We conducted a monocentric retrospective study including SEA patients treated with benralizumab for 1 year. Clinical, functional and inflammatory data were collected at baseline, 6 (T6) and 12 (T12) months. Results: Twenty-two SEA patients on benralizumab were included. We observed a reduction in exacerbations rate and systemic steroid treatment (p < 0.0001) as well as an improvement in asthma control (p < 0.0001), health-related quality of life (p = 0.017) and lung function pre-BD FEV1 (L) (p = 0.02) and percentage (p = 0.004) and post-BD FEV1 (L) (p = 0.01) and percentage (p = 0.003) from baseline to T6 and T12. A reduction in sputum eosinophil percentage was observed at T6 and T12 (p < 0.005). We found a positive correlation between the variation of sputum eosinophils percentage and FEV1 (L) at T12 (rho = −0.79, p = 0.04). Moreover, the improvement of FEF25%–75% from baseline to 6 (rho = −0.53, p = 0.03) and 12 (rho = −0.62, p = 0.01) months negatively correlated with the duration of asthma disease. In our cohort 12/22 patients were super-responders at T6 and 15/22 at T12. Furthermore, clinical remission was reached by 12/22, and all of them obtained blood and sputum eosinophils counts normalisation. Conclusion: Our data confirm that it is a rapid and effective treatment for SEA acting on clinical, functional, systemic and airway inflammatory outcomes. Our results highlight the role of induced sputum as a promising non-invasive technique to investigate pathophysiologic mechanisms in severe asthma treated with biologics. Finally, a negative correlation between small airway improvement and the duration of asthma may suggest that a prompt referral to asthma centres may delay lung function worsening. Additional studies are needed to investigate more in-depth the role of induced sputum in the management of asthma, response to treatment and remission. Plain language summary Analysis of the effect of a biological therapy on severe asthma Background: Asthma is estimated to affect almost 5%-8% of the European adult population, and 5%–10% of these patients suffer from a severe asthma form. Severe asthma is characterised by chronic airway inflammation despite traditional inhaled treatment and patients may experience acute flare ups requiring courses of steroids and eventually hospitalization leading to a poor quality of life. New biological drugs have been introduced to treat severe asthma characterized by inflammation in the blood and in the lungs. Benralizumab is a well known biological option for severe asthmatic patients. Methods: We provide data on 22 patients followed up in our tertiary severe asthma centre in Tradate, Italy, affected by severe eosinophilic asthma treated with benralizumab for at least one year. Results: Our data confirmed a rapid effect of benralizumab on respiratory symptoms, exacerbations and quality of life. In addition, we documented a significant improvement in lung function along with a normalization of inflammation in the blood and in the lungs, assessed with a non-invasive tool: the induced sputum. Conclusions: Interestingly, our data highlight the importance of induced sputum as a promising non-invasive technique to investigate pathophysiologic mechanisms in severe asthma treated with biologics. Additional studies are needed to implement its role in the management of asthma also in terms of response to treatment towards a personalized approach.